Fish diversity in the Nong Leng Sai Wetland, Phayao Province, Northern Thailand, after deep-water dredging - SIRILUCK TUNCHAROEN; KANOKPHON MANETAM; SITIPORN PORNPUANG; WARARITH CHAISAN; DUTRUDI PANPROMMIN; KANYANAT SOONTHORNPRASIT; SANTIWAT PITAKPOL (Society for Indonesian Biodiversity, 2024)
Abstract. Tuncharoen S, Manetam K, Pornpuang S, Chaisan W, Panprommin D, Soonthornprasit K, Pitakpol S. 2024. Fish diversity in the Nong Leng Sai Wetland, Phayao Province, Northern Thailand, after deep-water dredging. Biodiversitas 25: 2738-2746. This study aimed to explore changes in the diversity of fish species in the Nong Leng Sai Wetland, Mae Chai District, Phayao Province, Northern Thailand, after just completed deep-water dredging while shallow-water dredging is in progress. Therefore, three different gill net mesh sizes collected fish specimens from January to July 2022. The results showed that 25 species belong to 23 genera, 13 families from 7 orders, and 21 native and 4 introduced fish species. The fish comprised of the miscellaneous group was the most composed by weight and number, accounting for 45.5% and 52%, respectively, followed by the carp, 38.6% by weight and 45.6% by number. The fish diversity after dredging has decreased, including species and quantity, compared to the diversity reported before. Physical changes in the Nong Leng Sai Wetland resulted from deep water dredging, including increasing water depth, more water storage volume, increased turbidity, and lack of fish shelter and natural food, affecting the diversity of fish species. Furthermore, dredging has stimulated the recovery of aquatic ecosystems regarding water quality, habitat of aquatic animals, and appropriate natural food, which is important for increasing the diversity of fish species and quantities.